Brain stem adenosine receptors modulate centrally mediated hypotensive responses in conscious rats: A review - Nassar, Noha N.; Abdel-Rahman, Abdel A. (My University, 2014)
Abbreviations: A2A, adenosine subtype A2A receptor; A1, adenosine subtype A1 receptor; ABC, avidin biotin complex; ABD rat, aortic barodenervated rat; α2 AR, alpha 2 adrenergic receptor; αMNE, alpha methyl norepinephrine; ATP, adenosine triphosphate; BP, blood pressure; cAMP, cyclic adenosine monophosphate; CGS21680, 2-[4-[(2-carboxyethyl)phenyl]ethylaminophenyl]ethylamino]-5′-N-ethylcarboxamidoadenosine. Selective A2A receptor agonist; CNS, central nervous system; CPA, N6-cyclopentyladenosine. Selective A1 receptor agonist; DAG, diacylglycerol; DPCPX, 8-cyclopentyl-1,3-dipropylxanthine. Selective A1 receptor antagonist; I1, imidazoline subtype 1 receptor; I.C., intracisternal; IP3, Inositol Triphosphate; I.V., intravenous; JNK, C-Jun N-terminal kinase; L-NAME, Nω-nitro-l-arginine methyl ester hydrochloride. Non-selective nitric oxide synthase inhibitor; NOS, nitric oxide synthase; NO, nitric oxide; NTS, nucleus tractus solitarius; PC-PLC, phosphatidyl choline-selective phospholipase C; PC12 cells, pheochromocytoma cells; PD98059, selective extracellular signal regulated kinase inhibitor; ERK1/2, extracellular signal regulated kinase; PDE, phosphodiesterase; PKA, protein kinase A; RVLM, rostral ventrolateral medulla; SAPK, stress activated protein kinase; SCH58261, 5-amino-7-(2-phenylethyl)-2-(2-furyl)-pyrazolo[4,3-∈]-1,2,4-triazolo[1,5-c]pyrimidine. Selective adenosine A2A antagonist; SHR, spontaneously hypertensive rat; SND, sympathetic neuronal discharge; SO, sham operated = conscious normotensive rats; 8-SPT, 8-(p-sulfophenyl)-theophylline. Non-selective adenosine receptor blocker; WKY, Wistar Kyoto rat
Keywords: Imidazoline I1-receptor; Centrally mediated hypotension; Clonidine; Central adenosine receptors; Conscious rats; MAPK-NOS signaling